THE EFFECTIVENESS OF CONTEXTUAL-BASED YOGA LEARNING MODEL ON STUDENT CHARACTER - I Wayan Muliarta (Program Pascasarjana Universitas Negeri Jakarta, 2021)
Low fitness is a projection of low movement skills and student learning energy so that it is possible to experience a decrease in mastery of the values ​​of each subject. This study was to analyze the effectiveness of the contextual-based yoga learning model (PYBK) on the character of the VIII grade junior high school students. This study used a quantitative research design with the type of research, namely experimental with this research design following the basic pattern of experimental design with the design of the Post Test Only Control Group Design to determine the character of the students. This research was conducted in junior high schools with a population of 144 students divided into 5 classes. The research sample was taken by random sampling technique so that two classes were determined to be the sample of this study. Class A with 27 students as the control group and class D with 30 students as the experimental group. The method used to collect data in this study is non-test. The data analysis used is descriptive and inferential. The data obtained were analyzed using the prerequisite test and t test for different samples using the help of the SPSS 25.0 for Windows program. The results of the hypothesis testing conducted showed the significance level of the Character count of 0,000. This result is smaller than the significance (α) 0.05. This means that there is a significant difference between students who were taught with the contextual-based Yoga learning model (PYBK) and students who were not taught with contextual-based Yoga learning models, after learning PJOK with the PYBK model.